Wildlife forensics in nullifying the false accusation: a case to deal with raw meat. Issue 1 (2nd January 2019) - Jabin, Gul; Ghosh, Avijit; Basu, Shambadeb; Khatri, Hiren; Singh, Sujeet K.; Chandra, Kailash; Sharma, Lalit K.; Thakur, Mukesh
Abstract: Molecular tools have been used in wildlife forensics for species identification of indiscernible samples and to provide evidence against poaching of wildlife and illegal trade of their products. This study was undertaken in identifying a confiscated material that has been seized under the Wildlife (Protection) Act, 1972 of India suspecting that accused has poached a deer species of wild origin for local consumption. The sample was processed for DNA sequencing of the partial fragments of three mitochondrial genes, that is, Cytochrome b, 12S rRNA, and 16S rRNA genes. Surprisingly, generated sequences from the confiscated sample showed 99% homology with Bos indicus, and phylogenetic analysis also clustered the confiscated material with Bos indicus with high bootstrap support. This study upholds the evidence for accused as the suspicion of confiscated material being an illegal product was negated, and the raw meat of cattle was merely for consumption through reliable assessment and validation from a public database. This case study exhibits the value of DNA barcoding and molecular diagnostic techniques to decipher the morphologically altered materials in wildlife forensic cases.